Analisis Tahapan Kebijakan Pengoptimalan Pendapatan Daerah - Agustinus Imam Saputra; Jarot Limpato (Direktorat Sistem Perbendaharaan, 2021)
Abstract In the era of regional autonomy, local governments are expected to optimize their local revenue to finance the implementation of business process and public services. During the pandemic, local governments have to work harder and be prudent in exploring the potential for local revenue. Rural and Urban Land and Building Tax (RU-LBT) is one source of local revenue that can be extracted. This study investigates the success story of Yogyakarta City in improving the RU-LBT determination in 2020. This study uses a descriptive qualitative approach with the content analysis method. The results of this study show that Yogyakarta was going through a long process in the effort to determine RU-LBT which is supported by a reliable Sales Value of Tax Object (SVTO). Regulations related to the determination of RU-LBT are the Regional Medium-Term Development Plan, General Policy on Regional Revenue and Expenditure Budget, Regional Regulations, Mayor Regulations, and Mayor Decrees. The stimulus in PBB-P2 is concrete steps in mitigating the risk of public resistance affected by the increase in tax payable. Hence, other local governments can make Yogyakarta City as a